Isolation And Characterization Of Bacteriocin Producing Lactic Acid Bacteria - Liasi, Sahar Abbasi (2009)

(untitled)
Lactic acid bacteria (LAB) in fermented foods produce a large variety of compounds which give these products their characteristic flavor and color apart from improving its safety and quality. LAB with potential applications in food industry have been isolated from a local fermented food (budu) and characterized based on their morphological and biochemical characteristics. Gram-staining, catalase and gas production tests were performed for identification while API 50 CHL (BioMérieux) was used for the determination of species. Twelve isolates were identified as genus Lactobacillus (5 isolates of Lb. paracasei, 2 isolates of Lb. plantarum, one isolate of Lb. casei and 4 isolates of Lb. sp). The highest population was Lb. paracasei (41.67%). All isolates showed gram-positive, catalase negative and some positive results for homo-fermentative characteristics . Antibiotic sensitivity test of these twelve isolates of LAB to 24 different types of antibiotics was conducted using the disc diffusion method. Inhibition zone diameter was measured and calculated from the means of five determinations and expressed in terms of resistance or susceptibility. All LAB isolates from this product were resistant to colestin sulphate, streptomycin, amikacin, norfloxacin, nalidixic acid, mecillinam, sulphanethoxazole/ trimethoprim, and kanamycin but susceptible to erythromycin, ceftriaxone, chlomphenicol, tetracycline, ampicillin and nitrofurantion. The four isolates (Lb. casei LA17, Lb. plantarum LA22, Lb. pracasei LA07 and Lb. sp. LA19) were evaluated for their ability in producing bacteriocins. The inhibitory spectra of the isolates when evaluated against a range of gram-positive and gram-negative test microorganisms showed that antimicrobial substance from these isolates inhibit the growth of indicator microorganisms, such as Bacillus cereus, Lactococcus lactis, Staphylococcus aureus, Salmonella enterica, Listeria monocytogenes and Escherichia coli. Complete inactivation of antimicrobial activity from Lb. paracasei LA07 was observed after treatment of cell-free supernatant with proteinase K confirming its proteinaceous nature. Treatment with α-amylase inactivated the antimicrobial activity suggesting that bacteriocin could be glycosylated. Stability of the bacteriocins in the present of catalase enzyme ruled out the possibility of antagonistic activity of bacteriocins due to hydrogen peroxide or organic acids. Lipase caused only a slight reduction of bacteriocin activity, indicating that besides the proteinaceous subunit, some lipid components may also involve in antibacterial activity. The partially purified bacteriocin produced by Lb. paracasei LA07 has molecular weight of 10 kDa, based on SDS-PAGE analysis. The antibacterial activity of cell free supernatant was significantly increased by the addition SDS, Triton x-100, Tween 80 and Tween 20. On the other hand, the antibacterial activity was lost with the addition of EDTA. The influence of pH, temperature, and media composition on growth of Lb. paracasei LA07 and bacteriocin production was also conducted in shake flask culture. The highest bacteriocin production was obtained in cultivation using MRS, which was about 51%, 4%, 63 % and 22% higher than those obtained in BHI, M17 NB and TSB, respectively. Production of bacteriocin was also influenced by the cultivation temperature and the highest production was obtained at 30oC. Optimal pH for growth of Lb. paracasei LA07 and bacteriocin production was achieved at an initial pH of 8.5. Addition of (5 g/l) yeast extract and meat extract to MRS medium increased further the bacteriocin by about 8% and 5%. Supplementation with glucose at concentrations up to 10 g/l as the sole carbon source, gradually enhanced bacteriocin production, while higher concentrations (20 g/l) did not further increase bacteriocin production. Growth and bacteriocin production were not significantly affected by the agitation rate in either in anaerobic or in microaeration conditions. From this study, it can be concluded that the locally fermented fish product, budu contained LAB where the highest population was Lb. paracasei. The antimicrobial activity produced by the LAB isolated in this research could act as a potential barrier to inhibit the growth of spoilage bacteria and food-borne pathogens.